Hipopotasemia genética refractaria en la edad adulta - Adriana Bandeira; Miguel Gonzalez Santos; Behnam Moradi; Alcina Ponte; Paula Costa (Sociedade Galega de Medicina Interna, 2022)
Hypokalemia, despite its potential seriousness, is frequently encountered in clinical practice; with the majority of cases occurring in adulthood being rationalized by examining the triad losses: diuretics, vomiting and diarrhea, as inherited causes of hypokalemia with later onset are uncommon. Below we report a case of chronic and recurrent mild hypokalemia, in an adult patient with idiopathic congenital deafness. Early clinical and analytical findings pointed to a hereditary syndrome with augmented potassium renal excretion. Suspicion of a likely molecular basis motivated the analysis of the barttin's gene, revealing a G47R mutation in heterozygosity as well as a second mutation within an usually unaltered area. G47R mutation when in homozygosity is associated with an attenuated BSND (Bartter syndrome accompanied by sensorineural deafness) phenotype, questioning the clinical significance of the second mutation discovered.